2008
DOI: 10.1159/000143723
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pharmacologic Neuroprotection after Birth Asphyxia: Where Do We Stand?

Abstract: Perinatal hypoxia-ischemia or birth asphyxia is a serious complication with a high mortality and morbidity. For decades, neuroprotective options have been explored to reduce reperfusion and reoxygenation injury to the brain, which accounts for a substantial part of birth asphyxia-related brain damage. In this review, we focus on neuroprotective strategies with a long-term follow-up, reported in both experimental and clinical studies. Strategies related to modification of excitatory neurotransmitter production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 138 publications
0
32
0
Order By: Relevance
“…The combination of hypothermia and other pharmacologic strategies after birth asphyxia may improve long-term neurodevelopment (9). Erythropoietin (EPO) has been shown to reduce brain lesion volume in an experimental setting of neonatal HI (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…The combination of hypothermia and other pharmacologic strategies after birth asphyxia may improve long-term neurodevelopment (9). Erythropoietin (EPO) has been shown to reduce brain lesion volume in an experimental setting of neonatal HI (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…N eonatal hypoxic-ischemic (HI) brain injury occurs in [1][2][3][4] per 1000 live-born infants and is an important cause of cerebral palsy, epilepsy, and adverse developmental outcome (1,2). Experimental studies in newborn animals with HI showed that antioxidative, anti-inflammatory, and neurotrophic agents are neuroprotective (3,4).…”
mentioning
confidence: 99%
“…Experimental studies in newborn animals with HI showed that antioxidative, anti-inflammatory, and neurotrophic agents are neuroprotective (3,4). However, in clinical studies with newborns with HI encephalopathy, only mild hypothermia showed a modest neuroprotective effect if started within 6 h after birth in asphyxiated term newborns with moderate encephalopathy (5,6).…”
mentioning
confidence: 99%
“…H ypothermia (HT) is one of the most promising neuroprotective modalities against hypoxic ischemic encephalopathy (HIE) in neonatal brain (1). However, in neonates with severe HIE, little neuroprotection could be achieved using current HT protocols in which whole-body or head cooling is performed for 48 to 72 h by maintaining the core temperature within a range of 33.5 to 34.5°C (2)(3)(4)(5).…”
mentioning
confidence: 99%